Modeling future cliff-front waves during sea level rise and implications for coastal cliff retreat rates - H. Matsumoto; M. E. Dickson; W. J. Stephenson; C. F. Thompson; A. P. Young (Scientific Reports, 2024)
Abstract It is often assumed that future coastal cliff retreat rates will accelerate as global sea level rises, but few studies have investigated how SLR (sea level rise) might change cliff-front wave dynamics. Using a new simple numerical model, this study simulates the number and type (breaking, broken, or unbroken) of cliff-front waves under future SLR scenarios. Previous research shows breaking waves deliver more energy to cliffs than broken waves, and unbroken waves generate minimal impact. Here, we investigated six cliff-platform profiles from three regions (USA, New Zealand, and UK) with varied tidal ranges and wave climates. Model inputs included 2013–2100 hindcast/forecast incident wave height and tidal water level, and three future SLR scenarios. Results show the number of both cliff-front breaking and broken waves generally increase for a high-elevation (relative to tide) cliff-platform junction. In contrast, breaking/broken wave occurrence decrease by 38–92% for a near-horizontal shore platform with a low-elevation cliff-platform junction under a high SRL scenario, leading to high (96–97%) unbroken wave occurrence. Overall, results suggest the response of cliff-front waves to future SLR is complex and depends on shore platform geometries and SLR scenarios, indicating that future cliff retreat rates may not homogeneously accelerate under SLR.